Preparation method of organic-inorganic hybrid MFI type zeolite molecular sieve membrane
Through the preparation method of organic-inorganic hybrid MFI zeolite molecular sieve membrane, ultraviolet light is used to decompose organic matter to form an organic-inorganic hybrid structure, which solves the problems of high energy consumption of traditional zeolite membranes and difficulty in separating small molecule gases with pure silicon MFI zeolite membranes, and achieves highly selective small molecule gas separation.
Patent Information
- Application Number
- CN202511223276.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-29
- Publication Date
- 2025-09-30
- Estimated Expiration
- 2045-08-29
AI Technical Summary
Traditional zeolite membrane preparation technology consumes high energy and causes structural damage. Pure silicon MFI zeolite membrane is difficult to apply to the separation of small molecule gases, and the existing hydrophilic MFI zeolite membrane is not ideal in separating small molecule gas mixtures.
The preparation method of organic-inorganic hybrid MFI zeolite molecular sieve membrane is adopted. By encapsulating organic template and organic filler into the pores of zeolite molecular sieve membrane, and decomposing organic matter with ultraviolet light, an organic-inorganic hybrid structure is formed, and the pore size is precisely controlled.
It achieves highly selective separation of small molecule gases, broadens the application field of MFI zeolite membranes, and improves separation effects.
Smart Images

Figure CN120714451A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of gas separation, and in particular to a method for preparing an organic-inorganic hybrid MFI type zeolite molecular sieve membrane. The method can improve the separation selectivity of the zeolite membrane for small molecule gases and can be widely used in gas purification, industrial gas separation and other occasions. Background Art
[0002] Zeolite molecular sieve materials have a regular pore structure, typically with molecular-scale pore sizes, allowing them to separate molecules of different sizes. Therefore, zeolite membranes are widely used as high-performance porous separation materials in gas separation and pervaporation. However, conventional zeolite membrane preparation techniques typically rely on the complete decomposition of organic templates under high-temperature conditions to fully open the zeolite membrane pores. This high-temperature treatment method is not only energy-intensive but also can partially damage the zeolite membrane structure, compromising its separation performance.
[0003] Pure silica MFI zeolite membranes have strong hydrophobicity and relatively large pore sizes (~0.55 nm), making them generally difficult to use for the dehydration and separation of organic compounds and the separation of small gas molecules. Chinese patent CN119461408A discloses an MFI zeolite membrane with an all-silica framework and hydrophilic pore walls, as well as its preparation method and application. This MFI zeolite membrane encapsulates hydrophilic small organic molecules within the molecular sieve pores, enabling tunable pore size and effectively increasing the hydrophilicity of the membrane's permeation channels. Compared to conventional MFI zeolite membranes, this zeolite membrane combines superior acid resistance with a smaller average pore size and excellent hydrophilicity, making it suitable for the efficient dehydration and separation of organic compounds, particularly for the separation of water / organic mixtures in strongly acidic environments. However, the MFI zeolite membranes prepared by this method have been less than ideal for the separation of small gas mixtures. Summary of the Invention
[0004] In order to solve the above problems, the present invention provides a method for preparing an organic-inorganic hybrid MFI type zeolite molecular sieve membrane.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions: A method for preparing an organic-inorganic hybrid MFI zeolite molecular sieve membrane comprises the following steps: (1) Encapsulating the organic template and the organic filler into the pores of the zeolite molecular sieve membrane; (2) Irradiating the zeolite molecular sieve membrane encapsulated with the template and the organic filler with ultraviolet light to partially decompose the organic molecules in the pores to form a zeolite molecular sieve membrane with an organic-inorganic hybrid structure.
[0006] Preferably, the specific method of step (1) is: placing the carrier into a synthesis solution containing a template and an organic filler, and encapsulating the template and the organic filler into the pores of the synthesized zeolite molecular sieve membrane through hydrothermal crystallization.
[0007] Preferably, the organic filler in step (1) is dimethylamine, trimethylamine, pentylamine, hexylamine, heptylamine, cyclohexylamine, N,N-dimethylethanolamine, N-methylpentylamine, N-ethylformamide, or dimethylethylenediamine. Further preferably, the organic filler is trimethylamine, cyclohexylamine, or N,N-dimethylethanolamine.
[0008] Preferably, the template in step (1) is tetrapropylammonium chloride (TPACl).
[0009] Further preferably, the synthesis liquid in step (1) is a mixture of tetraethyl orthosilicate, a template, a filler, sodium hydroxide, and water, and the molar ratio of tetraethyl orthosilicate, template, filler, sodium hydroxide, and water is 1:0.05-2:0.01-4:0.05-0.4:20-150. Further preferably, the molar ratio of tetraethyl orthosilicate, template, filler, sodium hydroxide, and water is 1:0.1-1:0.1-2:0:1-0.3:40-100. Even more preferably, the molar ratio is 1:0.25-0.3:0.1-0.3:0.15-0.2:60-100.
[0010] Preferably, the hydrothermal crystallization conditions in step (1) are: 120-200°C, 10-60h, more preferably 140-180°C, 12-48h.
[0011] Preferably, the wavelength of the ultraviolet light in step (2) is 100-400 nm, more preferably 185-254 nm.
[0012] Preferably, the UV irradiation intensity in step (2) is 0.01-100 mW / cm². More preferably, it is 0.1-40 mW / cm². More preferably, it is 1-10 mW / cm².
[0013] Preferably, the ultraviolet irradiation time in step (2) is 1-300 hours, more preferably 40-120 hours.
[0014] Preferably, the ultraviolet light irradiation temperature in step (2) is 0-100°C, more preferably 20-70°C, and even more preferably 25-40°C.
[0015] Preferably, the average pore size of the organic-inorganic hybrid zeolite molecular sieve membrane obtained after the decomposition of the organic molecules in step (2) is 0.3-0.5 nm.
[0016] The present invention also provides the use of the organic-inorganic hybrid zeolite molecular sieve membrane prepared by the above method in gas separation. The gases described are He, H2, CO2, N2, CH4, C2H6, C3H8, and SF6. Preferably, it is more suitable for separating CO2 / CH4, N2 / SF6, and H2 / CH4. The selectivities can reach 82, 114, and 55, respectively. The CO2 permeability is 2×10 -7 mol·Pa -1 ·s -1 ·m -2 , N2 permeability can reach 6.5×10 -8 mol·Pa -1 ·s -1 ·m -2 , H2 permeability is 3.1×10 -7 mol·Pa -1 ·s -1 ·m -2 .
[0017] Beneficial effects of the present invention: For water / organic separation systems, regulating the surface chemistry of zeolite membranes is particularly important. However, for the separation of small molecule gases, the control precision required for the membrane's average pore size and pore size distribution is far higher than that required for water / organic separation systems. Achieving efficient separation of small molecule gas mixtures using mesoporous MFI zeolite membranes requires further screening of the organic molecules encapsulated in the MFI zeolite membrane's pores and more precise control of their decomposition behavior, thereby achieving precise control of the zeolite membrane's pore structure.
[0018] By selecting an ideal template and organic filler, encapsulating them in situ within the pores of an MFI zeolite membrane and then subjecting them to radiolysis, the method enables precise subnanometer-scale control of the zeolite membrane's pore size, bringing the effective pore diameter of the mesoporous MFI zeolite membrane close to the pore size. The uniform pore structure and narrow pore size distribution enable extremely high selectivity for the separation of small molecule gases, significantly expanding the application of MFI zeolite membranes. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 1 is the XRD pattern of the carrier, the seed layer coated carrier and the synthesized MFI zeolite membrane in this Example 1.
[0020] Figure 2 These are SEM images of the support (a, d), the seed layer-coated support (b, e) and the MFI zeolite membrane (c, f) in Example 1. DETAILED DESCRIPTION
[0021] The raw materials used in the examples and comparative examples of the present invention are all common commercially available products.
[0022] Example 1 Preparation of organic-inorganic hybrid MFI zeolite molecular sieve membrane: (1) Loading the seed crystals on an alumina carrier: Tetrapropylammonium hydroxide (TPAOH) and deionized water were mixed evenly, and then tetraethyl silicate (TEOS) solution was dropped into the mixture. The mixture was stirred at 600 rpm for 6 h to obtain a synthetic solution with a molar ratio of 1.0 TEOS: 5 TPAOH: 10 H2O.
[0023] The synthesis solution was transferred to a reactor and hydrothermally crystallized at 150°C for 48 hours. The resulting product was repeatedly washed with deionized water until neutral and ultrasonically dispersed in deionized water to prepare a 1.5 mg / mL seed solution. The seed crystals were loaded onto an alumina support (average pore size 200 nm) by impregnation and subsequently calcined in a muffle furnace at 500°C for 8 hours to obtain a support pre-coated with a seed layer.
[0024] (2) Encapsulation of organic templates and organic fillers: A synthesis solution with a molar ratio of 1.0 TEOS: 0.3 TPACl: 0.1S: 0.2NaOH: 60 H2O (where S is the filler trimethylamine) was prepared. This solution, along with a pre-seeded support, was placed in a reactor and hydrothermally crystallized at 180°C for 24 hours. After the reaction, the zeolite membrane was removed and rinsed with deionized water until neutral. Finally, the water was dried to obtain the synthesized MFI zeolite membrane.
[0025] (3) Ultraviolet radiation treatment: The MFI zeolite membrane was placed under a UV lamp with a wavelength of 254 nm and irradiated for 48 h (10 mw / m 2 ; 25℃) to partially decompose the organic matter in the pores of the zeolite membrane, and finally obtain an organic-inorganic hybrid MFI zeolite molecular sieve membrane.
[0026] Figure 1 The XRD patterns of the alumina support, the support pre-coated with seed crystals, and the synthesized MFI zeolite membrane used in this Example 1 show that the characteristic diffraction peaks of the synthesized MFI membrane are completely consistent with the standard card of MFI zeolite (PDF#44-0696), and no other impurity peaks are observed. This confirms that high-purity MFI zeolite molecular sieves were successfully prepared in this Example. Figure 2 (a) is the SEM image of the carrier surface. Figure 2 (d) is the SEM characterization picture of the carrier cross section, from which it can be seen that the pores on the carrier surface are relatively large. Figure 2(b, e) are SEM images of the surface and cross-section of a support coated with a seed layer. It can be seen that after the seed layer is applied, the original pore structure of the support is filled, and the support surface becomes smooth. The seed crystal particle size is approximately 200 nm, and the seed layer thickness is approximately 2 μm. Figure 2 (c, f) are SEM images of the synthesized MFI zeolite membrane. It can be seen that the grains of the MFI membrane grow alternately. The thickness of the MFI zeolite membrane is about 8 μm, and the surface has no obvious defects and is dense.
[0027] To evaluate the permeability and selectivity of the zeolite membrane, the prepared organic-inorganic hybrid MFI zeolite molecular sieve membrane was placed in a stainless steel membrane assembly and sealed with an O-ring. The single gas permeability of the membrane was measured at room temperature with an inlet pressure of 0.2 MPa and a permeate pressure of 0.1 MPa. The CO2 permeability of the organic-inorganic hybrid MFI zeolite molecular sieve membrane was 2×10 - 7 mol·Pa -1 ·s -1 ·m -2 , CO2 / CH4 selectivity is 82.
[0028] Example 2 Preparation of organic-inorganic hybrid MFI zeolite molecular sieve membrane: (1) The preparation of the seed layer on the alumina carrier is the same as in Example 1.
[0029] (2) A synthetic solution with a molar ratio of 1.0 TEOS:0.25 TPACl:0.3 S:0.15 NaOH:70H2O (where S is the filler cyclohexylamine) was prepared and placed in a reactor with a carrier pre-coated with seed crystals. Hydrothermal crystallization was performed at 160°C for 36 hours. After the reaction, the zeolite membrane was removed and rinsed with deionized water until neutral. Finally, the water was dried to obtain the synthesized MFI zeolite membrane. (3) Place the MFI zeolite membrane under a UV lamp with a wavelength of 185 nm and irradiate it for 120 h (4 mw / m 2 ; 40℃) to partially decompose the organic matter in the pores of the zeolite membrane, and finally obtain an organic-inorganic hybrid MFI zeolite molecular sieve membrane.
[0030] The method for evaluating the permeability and selectivity of the organic-inorganic hybrid MFI zeolite molecular sieve membrane was the same as that in Example 1. The N2 permeability of the organic-inorganic hybrid MFI zeolite molecular sieve membrane was 6.5×10 -8 mol·Pa -1 ·s -1 ·m -2 , N2 / SF6 selectivity is 114.
[0031] Example 3 (1) The preparation of the seed layer on the alumina carrier is the same as in Example 1.
[0032] (2) A synthetic solution with a molar ratio of 1.0 TEOS: 0.3 TPACl: 0.2S: 0.2 NaOH: 100H2O (where S is the filler N,N-dimethylethanolamine) was prepared. This solution and the pre-seeded carrier were placed in a reactor and hydrothermally crystallized at 160°C for 36 hours. After the reaction, the zeolite membrane was removed and rinsed with deionized water until neutral. Finally, the water was dried to obtain the synthesized MFI zeolite membrane.
[0033] (3) The MFI zeolite membrane was placed at 0.3 cm below a UV lamp with a wavelength of 254 nm and irradiated for 72 h (1 mw / m 2 ; 30℃) to partially decompose the organic matter in the pores of the zeolite membrane, and finally obtain an organic-inorganic hybrid MFI zeolite molecular sieve membrane.
[0034] The method for evaluating the permeability and selectivity of the organic-inorganic hybrid MFI zeolite molecular sieve membrane was the same as that in Example 1. The H2 permeability of the organic-inorganic hybrid MFI zeolite molecular sieve membrane was 3.1×10 -7 mol·Pa -1 ·s -1 ·m -2 , H2 / CH4 selectivity is 55.
[0035] Comparative Example 1 Compared with Example 1, the difference is that step (3) uses a high-temperature calcination method to decompose organic matter in the pores of the MFI zeolite membrane.
[0036] The MFI zeolite membrane was placed in a muffle furnace and heated to 500°C at a rate of 0.5°C / min in an air atmosphere for 8 h, and then cooled to room temperature at a rate of 0.5°C / min. The CO2 permeability of the obtained organic-inorganic hybrid MFI zeolite molecular sieve membrane was 8.4×10 - 7 mol·Pa -1 ·s -1 ·m -2 , but its CO2 / CH4 selectivity is only 5.5, indicating that the average pore size of the zeolite molecular sieve membrane is large.
[0037] Comparative Example 2 Compared with Example 2, the difference is that, except for the high-temperature calcination method to decompose the organic matter in the pores of the MFI zeolite membrane, the other preparation conditions of the MFI zeolite membrane are the same as those of Example 2. The calcination process is as follows: the MFI zeolite membrane is placed in a muffle furnace and heated to 500°C at 0.5°C / min in an air atmosphere for 8 hours, and then cooled to room temperature at 0.5°C / min. The N2 permeability of the obtained MFI membrane is 2.6×10-7 mol· Pa -1 ·s -1 ·m -2 , but its N2 / SF6 selectivity is only 3.2, indicating that the average pore size of the zeolite molecular sieve membrane is large.
[0038] Comparative Example 3 The difference from Example 3 is: N,N-dimethylethanolamine was not added to the synthesis solution in step (2). The H2 permeability of the obtained organic-inorganic hybrid MFI zeolite molecular sieve membrane was 3.3×10 -7 mol·Pa-1·s -1 ·m -2 , but its H2 / CH4 selectivity is only 7.5, indicating that the average pore size of the zeolite molecular sieve membrane is large.
[0039] Comparative Example 4 Compared with Example 2, the difference is that cyclohexylamine is not added to the synthesis solution in step (2). The N2 permeability of the obtained organic-inorganic hybrid MFI zeolite molecular sieve membrane is 4.2×10 -8 mol·Pa -1 ·s -1 ·m -2 , but its N2 / SF6 selectivity is only 25, indicating that the average pore size of the zeolite molecular sieve membrane is large.
[0040] Comparative Example 5 The difference from Example 3 is that, according to Chinese patent document CN119461408A, ozone atmosphere is used to decompose organic matter in the pores of the MFI zeolite membrane.
[0041] The ozone decomposition process of organic matter in the pores of the MFI zeolite membrane is as follows: the MFI zeolite membrane is placed in a tube furnace and heated to 150°C at a rate of 0.5°C / min. Then, an ozone / oxygen mixture is introduced into the tube furnace and maintained for 20 hours. The temperature is then cooled to room temperature at a rate of 0.5°C / min. The H2 permeability of the resulting MFI zeolite membrane is 4.6×10 -7 mol·Pa -1 ·s -1 ·m -2 , the H2 / CH4 selectivity is only 4.3, indicating that the average pore size of the zeolite molecular sieve membrane is large.
Claims
1. A method for preparing an organic-inorganic hybrid MFI type zeolite molecular sieve membrane, characterized in that: The following steps are involved: (1) Encapsulating the organic template and the organic filler into the pores of the zeolite molecular sieve membrane; (2) Irradiating the zeolite molecular sieve membrane encapsulated with the template and the organic filler with ultraviolet light to partially decompose the organic molecules in the pores to form a zeolite molecular sieve membrane with an organic-inorganic hybrid structure.
2. The preparation method according to claim 1, characterized in that The specific method of step (1) is: placing the carrier into a synthesis solution containing a template and an organic filler, and encapsulating the template and the organic filler into the pores of the synthesized zeolite molecular sieve membrane through hydrothermal crystallization.
3. The preparation method according to claim 1, characterized in that The organic filler described in step (1) is dimethylamine, trimethylamine, pentylamine, hexylamine, heptylamine, cyclohexylamine, N,N-dimethylethanolamine, N-methylpentylamine, N-ethylformamide, and dimethylethylenediamine.
4. The preparation method according to claim 3, characterized in that The organic filler is trimethylamine, cyclohexylamine, and N,N-dimethylethanolamine.
5. The preparation method according to claim 1, characterized in that Preferably, the template in step (1) is tetrapropylammonium chloride.
6. The preparation method according to claim 2, characterized in that The synthetic liquid in step (1) is a mixture of ethyl orthosilicate, a template, a filler, sodium hydroxide, and water, and the molar ratio of ethyl orthosilicate, template, filler, sodium hydroxide, and water is 1:0.05-2:0.01-4:0.05-0.4:20-150.
7. The preparation method according to claim 6, characterized in that The molar ratio of ethyl orthosilicate, template, filler, sodium hydroxide and water is 1:0.1-1:0.1-2:0:1-0.3:40-100.
8. The preparation method according to claim 2, characterized in that The hydrothermal crystallization conditions in step (1) are: 120-200°C, 10-60 h.
9. The preparation method according to claim 1, characterized in that The wavelength of the ultraviolet light described in step (2) is 100-400 nm; the ultraviolet light irradiation intensity is 0.01-100 mW / cm², the ultraviolet light irradiation time is 1-300 hours, and the ultraviolet light irradiation temperature is 0-100°C.
10. The preparation method according to claim 9, characterized in that The ultraviolet light wavelength in step (2) is 185-254 nm, the ultraviolet light irradiation intensity is 0.1-40 mW / cm², the ultraviolet light irradiation time is 40-120 h, and the ultraviolet light irradiation temperature is 20-70 ° C.
Citation Information
Patent Citations
Zeolite membrane for high-efficiency separation of CO2 as well as preparation method and application of zeolite membrane
CN116889805A
MFI Molecular Sieve Composition and the Method of Making the Same
US20110009685A1